Integration of ICTs in reading and writing teaching and learning in college. (2020)
This chapter reviews the current incorporation of Information and Communication Technologies (ICT) in colleges, specifically in the area of reading and writing, as compiled in a series of studies published between 2013 and 2019. The purpose is to compare those results with the Guidelines for learning and teaching aimed at improving student performance in the course Reading Comprehension and Writing at the Andrés Bello Catholic University (UCAB). Such guidelines are the result of an investigation carried out as a master’s degree Project, “The written composition of argumentative texts in novice-students and teacher-experts” (Salazar, 2018). This link contributes to the enrichment of teaching-learning strategies for reading and writing, by concluding that ICTs can be incorporated for teacher training, teaching in real situations, establishing the “Draft Policy”, the definition of explicit evaluation criteria, the execution of mentoring programs, and the dissemination of tools to prevent or confront procrastination.